Os Odontoideum (OO): A Rare Cause of Cervical Myelopathy- Reports of two cases (Bangladesh Journal of Child Health, 2020)
Os odontoideum (OO) is a rare condition defined radiographically as an oval or round-shaped ossicle of variable size with smooth circumferential cortical margins representing the odontoid process that has no continuity with the body of second cervical vertebra (C2). Since the upper cervical spinal region is complex from anatomical point of view and has many vital structures passing in close relation to each other it is important to review this topic. If a person suffers from hyper mobile dens due to insuffiency of its ligamentous complex, it may cause translation of the atlas on the axis and may compress the cervical cord or vertebral arteries. However, patients with this condition may be asymptomatic or may be symptomatic of a variety of neurological deficits and vascular dysfunctions. There are cases where patients suffering from Os odontoideum became quadriplegic after a minor trauma. The treatment of both the asymptomatic and symptomatic characteristics of this condition has undergone changes over the past few decades. In our paper we present two cases who presented as spastic quadriplegia, then was diagnosed as Os odontoideum (OO) and treated.Bangladesh J Child Health 2020; VOL 44 (2) :118-121